Muir-Torre syndrome: the curious case of wobbly microsatellites and their mucosal Lynch - Elmore, Robert A.; Dick, Mary K.; Sharma, Poonam K. (International Journal of Research in Dermatology, 2019)
MSH2 mismatch repair gene is commonly associated with Lynch syndrome; however, Lynch syndrome’s phenotypic variant, Muir-Torre syndrome is a lesser known entity comprising a spectrum of benign to malignant sebaceous neoplasms and is often the first etiology of a more significant prodromal syndrome. Both syndromes encompass gastrointestinal, genitourinary tract, and prostatic pathologies. We present a 15-year patient progression starting with new sebaceous hyperplasia and congenital melanocytic nevus skin lesions presenting in a 38-year-old caucasian male. After approximately four years additional cutaneous lesions began continuously appearing identified as: ulcerated sebaceoma, basal cell carcinoma, sebaceous hyperplasia, sebaceous adenoma, and hidradenoma. The patient went on to develop prostate adenocarcinoma and tubular adenoma of the ascending colon and rectum. Immunohistochemical staining demonstrated MSH2 and MSH6 instability and patient was recommended for Lynch Syndrome genetic testing. Later genetic analysis showed pathologic variant of MSH2 confirming Muir-Torre Syndrome. When multiple pathologies are involved that affect ectoderm differentiation, a diagnostic workup for microsatellite instability is recommended in association with a genetic counselor consultation. When a familial defect in a DNA repair enzyme (MSH1, MSH2, etc.) is known, we recommend PCR amplification for microsatellite instability in offspring between ages 5-15 to reduce morbidity and mortality in this population.